Physiotherapy Approaches in ACL Reconstruction Rehabilitation: A Narrative Review of Evidence-Based Practices - Pathan, Umiya I.; Sharma, Shimpa (Journal of Neonatal Surgery, 2025)
Background Anterior cruciate ligament (ACL) injuries are common among athletes and active individuals, often requiring surgical reconstruction to restore knee stability. Effective rehabilitation is crucial for optimizing recovery, restoring function, and ensuring a safe return to physical activities and sports. Various physiotherapy approaches have been developed to enhance post-surgical recovery, incorporating progressive loading, neuromuscular training, and functional exercises. Objective This narrative review aims to explore evidence-based physiotherapy interventions in ACL reconstruction rehabilitation, focusing on key phases, best practices, and emerging trends. The review highlights strategies that enhance knee stability, reduce reinjury risk, and optimize return to sport outcomes. Methodology A comprehensive review of the literature on ACL rehabilitation was conducted using peer-reviewed journals, clinical guidelines, and systematic reviews. The selected studies emphasize physiotherapy interventions across different rehabilitation phases, including early mobilization, strength training, neuromuscular re-education, and functional training. Special attention is given to novel approaches such as blood flow restriction (BFR) training, psychological readiness assessment, and technology-assisted rehabilitation. Conclusion ACL rehabilitation requires a structured, progressive approach that aligns with physiological healing and functional demands. Evidence-based physiotherapy practices, incorporating strength training, neuromuscular control, and sport-specific exercises, enhance recovery outcomes and reduce the risk of re-injury. Personalized rehabilitation strategies, including psychological support and emerging technologies, can further optimize patient outcomes. Future research should focus on refining rehabilitation protocols and integrating innovative interventions for improved recovery